Spontaneous peritonitis of pyelo-reno-ureteral origin - Clarck, Omar; Farcic, Antonio; Estefan, Alberto (Cirugía del Uruguay, 1972)
The paper describes two cases of spontaneous peritonitis of reno-pyelo-ureteral origin; one of them is the first case in national literature diagnosed prior to operation. Cases recorded in the country are revised with respect to their ethiopathogenesis and pathological anatomy, with the emphasis in the elements of clinical and operatory diagnosis. Ihe adequate surgical tactics are discussed, since they constitute a fundamental factor in the prognosis of this serious complication of high urinary pathology which eht urgency surgeon faces almost constantly.